Antimicrobial and Antioxidant Activities of Methanol and Hexane Extract of Some Endemic Astragalus Species - GULLUCE, MEDINE; SOKMEN, MUNEVVER; AGAR, GULERAY; ADIGUZEL OZLEM BARIS, AHMET; SAHIN, FIKRETTIN (Asian Journal of Chemistry, 2010)
The present study is related to evaluate antimicrobial and antioxidant activities of hexane and methanol extracts of four endemic Astragalus species grown in the vicinity of Erzurum, located in the eastern Anatolia, Turkey. Methanol extract of Astragalus species exhibited better free radical scavenging activity providing 50 % inhibition at the concentration in the range of 21.0-250.3 μg/mL. In the case of β-carotene-linoleic acid system, both extracts obtained from A. campylosema and A. cristianus were active among studied Astragalus species. A. campylosema root extracts completely inhibit the oxidation of linoleic acid in the studied test systems. On the other hand, the extracts obtained from Astragalus species tested have been evaluated for their possible in vitro antibacterial, anticandidal and antifungal activities based on disk diffusion assay. The results suggested that none of the extracts have antimicrobial activity on the microorganisms tested.